300 - Miller, Frank 1957- (Dark Horse Books, 2006)
The armies of Persia -- a vast horde greater than any the world has ever known -- are poised to crush Greece, an island of reason and freedom in a sea of madness and tyranny. Standing between Greece and this tidal wave of destruction is a tiny detachment of but three hundred warriors. But these warriors are more than men -- they are Spartans!